Association Between Male fertility and Vitamin D - Ewa Piekarska; Mateusz Pawlicki; Anna Łopuszyńska; Magdalena Kozioł; Aleksandra Krasa; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2021)
Introduction: Infertility affects millions of people of reproductive age worldwide. Male infertility may be caused by a number of different factors including problems in the ejection of semen, absence or low levels of sperm, or abnormal morphology and movement of the sperm. Environmental and lifestyle factors also have a meaningful impact on male reproductive system. Fertility care should include the prevention, diagnosis and treatment of the disorder. That is why numerous studies have explored the role of vitamin D in regulating the functioning of the reproductive system. Aim of study: Investigation of correlation between Vitamin D and male fertility. Results: Studies consistently show that Vitamin D deficiency has a negative influence on male fertility. Number of trials show that the mean value of Vitamin D serum levels tend to be significantly lower in infertile men compared to fertile men. Vitamin D insufficiency and deficiency has been noticed to be associated with poor semen quality (lower sperm concentrations, lower motility). It became  evident that vitamin D exhibits positive correlation with the male fertility by maintaining the levels of sex hormones, down regulating oxidative stress and up regulating oxidative defence. Supplementation of Vitamin D may improve the quality and function of sperm by increasing its motility and concentration. Conclusions: Although Vitamin D supplementation cannot be considered for treatment of male infertility itself, physicians should take the vitamin serum levels under consideration while providing treatment for infertile male patients.